2009
DOI: 10.1128/aac.00022-09
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of EDP-420 after Multiple Oral Doses in Healthy Adult Volunteers and in a Bioequivalence Study

Abstract: EDP-420 (also known as EP-013420, or S-013420) is a first-in-class bridged bicyclolide currently in clinical development for the treatment of respiratory tract infections (RTI) and has previously shown favorable pharmacokinetic (PK) and safety profiles after the administration of single oral doses of a suspension to healthy volunteers. Here we report its PK profile after the administration of multiple oral doses of a suspension to healthy adults. Bioequivalence between suspension and capsule formulations, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…The KC 50 /MIC values in this study were generally higher than those for β‐lactams, suggesting that this parameter could be an index of dose dependency for the efficacy, as suggested by Yano et al The KC 50 values of modithromycin ranged from 0.159 to 473 μg/mL. Plasma C max following a 100–1200‐mg single oral dose in the US phase 1 study ranged from 196 to 1076 μg/mL, indicating KC 50 values were achievable in in vivo plasma.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The KC 50 /MIC values in this study were generally higher than those for β‐lactams, suggesting that this parameter could be an index of dose dependency for the efficacy, as suggested by Yano et al The KC 50 values of modithromycin ranged from 0.159 to 473 μg/mL. Plasma C max following a 100–1200‐mg single oral dose in the US phase 1 study ranged from 196 to 1076 μg/mL, indicating KC 50 values were achievable in in vivo plasma.…”
Section: Discussionsupporting
confidence: 63%
“…For S. aureus SR20405 and H. influenzae SR24169, PK parameter sets P1–P4, which were determined based on PK parameters estimated from plasma concentrations of modithromycin following a 400‐mg single oral dose in Phase 1 study conducted in US, were used. For S. pneumoniae SR26132, PK parameter set P5, which was determined based on PK parameters estimated from plasma concentrations of modithromycin following a 300‐mg single oral dose in Phase 1 study conducted in Japan, was used.…”
Section: Methodsmentioning
confidence: 99%
“…The time-concentration curves of S-013420 exposed to H. influenzae were basically derived from the PK profile of S-013420 after administration of a 400-mg single oral dose obtained from a phase I study conducted in the United States (15). The AUC 0-24 , C max , and half-life (t 1/2 ) of this PK profile were 8.61 g-h/ml, 0.506 g/ml, and 17.8 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with telithromycin, EDP-420 also showed excellent pharmacokinetic properties in mice, rat and dog with longer half-life and higher concentration in lung. Disclosed clinical data [58,59] showed that EDP-420 was well tolerated in healthy human volunteers with long half-life and high systemic exposure. EDP-420 also exhibited excellent activities against Mycobacterium avium [60,61] and penicillin-resistant and quinolone-and penicillin-resistant pneumococci [62].…”
Section: Novel Bicyclolidesmentioning
confidence: 97%